Conversion to Secondary Progressive Multiple Sclerosis: Patient Awareness and Needs. Results From an Online Survey in Italy and Germany - Solari, Alessandra; Giovannetti, Ambra Mara; Giordano, Andrea; Tortorella, Carla; Torri Clerici, Valentina; Brichetto, Giampaolo; Granella, Franco; Lugaresi, Alessandra; Patti, Francesco; Salvetti, Marco; Pesci, Ilaria; Pucci, Eugenio; et al. (Frontiers in Neurology, 2019)
Background: Few studies have investigated the experiences of patients around the conversion to secondary progressive multiple sclerosis (SPMS). ManTra is a mixed-method, co-production research project conducted in Italy and Germany to develop an intervention for newly-diagnosed SPMS patients. In previous project actions, we identified the needs and experiences of patients converting to SPMS via literature review and qualitative research which involved key stakeholders. Aims: The online patient survey aimed to assess, on a larger and independent sample of recently-diagnosed SPMS patients: (a) the characteristics associated to patient awareness of SPMS conversion; (b) the experience of conversion; (c) importance and prioritization of the needs previously identified. Methods: Participants were consenting adults with SPMS since ≤5 years. The survey consisted of three sections: on general and clinical characteristics; on experience of SPMS diagnosis disclosure (aware participants only); and on importance and prioritization of 33 pre-specified needs. Results: Of 215 participants, those aware of their SPMS diagnosis were 57% in Italy vs. 77% in Germany (p = 0.004). In both countries, over 80% of aware participants received a SPMS diagnosis from the neurologist; satisfaction with SPMS disclosure was moderate to high. Nevertheless, 28–35% obtained second opinions, and 48–56% reported they did not receive any information on SPMS. Participants actively seeking further information were 63% in Germany vs. 31% in Italy (p < 0.001). Variables independently associated to patient awareness were geographic area (odds ratio, OR 0.32, 95% CI 0.13–0.78 for Central Italy; OR 0.21, 95% CI 0.08–0.58 for Southern Italy [vs. Germany]) and activity limitations (OR 7.80, 95% CI 1.47–41.37 for dependent vs. autonomous patients). All pre-specified needs were scored a lot or extremely important, and two prioritized needs were shared by Italian and German patients: “physiotherapy” and “active patient care involvement.” The other two differed across countries: “an individualized health care plan” and “information on social rights and policies” in Italy, and “psychological support” and “cognitive rehabilitation” in Germany. Conclusions: Around 40% of SPMS patients were not aware of their disease form indicating a need to improve patient-physician communication. Physiotherapy and active patient care involvement were prioritized in both countries.